Investigation the effect of ramelteon on urinary bladder smoth muscle contraction-relaxation mechanism - Serhatlioglu, İhsan; Hekım, Munevver Gizem; Zorlu, Gokhan; Bulmus, Ozgur; Yasar, Abdullah; Serhatlıoğlu, Ihsan; Kacar, Emine (My University, 2022)
Aim: A melatonin receptor agonist ramelteon is a drug that is also used in urinary tract\rinfections. Melatonin is known to have an effect on smooth muscle contraction. In this\rstudy, we aimed to question whether ramelteon exerts a melatonin-like effect on bladder\rcontractions.\rMaterial and Methods: Wistar-albino (n = 8) intact female rats were used in the study.\rAfter decapitation, 1.5x5 mm bladder strips were examined in an isolated organ bath in\rwhich there was Krebs-Henseleit solution. After the regulation period, ramelteon was\rapplied non-cumulatively in two separate doses of 0.2?M, 1?M. The area under the curve\r(AUC) and peak to peak (p-p) values before and after the application were normalized as\r% change.\rResults: Exposure of bladder strips to ramelteon significantly increased contractions.\rRamelteon caused a statistically significant increase in p-p, AUC values of spontaneous\rbladder contractions at a dose of 0.2 and 1?M (p < 0.05).\rConclusion: Ramelteon has an activator effect on spontaneous bladder contractions\runlike melatonin. The physiopathological mechanisms under activator activity need to be\rinvestigated with further studies. This effect should be taken into account in clinical use.
Keywords: Biyoloji; Tıbbi Araştırmalar Deneysel; Genel ve Dahili Tıp; Fizyoloji